Post‐Transcriptional Regulation of the Human Mu‐Opioid Receptor (MOR) by Morphine‐Induced RNA Binding Proteins hnRNP K and PCBP1 - Song, Kyu Young; Choi, Hack Sun; Law, Ping‐Yee; Wei, Li‐Na; Loh, Horace H. (Journal of cellular physiology, 2017)
Expression of the mu‐opioid receptor (MOR) protein is controlled by extensive transcriptional and post‐transcriptional processing. MOR gene expression has previously been shown to be altered by a post‐transcriptional mechanism involving the MOR mRNA untranslated region (UTR). Here, we demonstrate for the first time the role of heterogeneous nuclear ribonucleic acids (hnRNA)‐binding protein (hnRNP) K and poly(C)‐binding protein 1 (PCBP1) as post‐transcriptional inducers in MOR gene regulation. In the absence of morphine, a significant level of MOR mRNA is sustained in its resting state and partitions in the translationally inactive polysomal fraction. Morphine stimulation activates the downstream targets hnRNP K and PCPB1 and induces partitioning of the MOR mRNA to the translationally active fraction. Using reporter and ligand binding assays, as well as RNA EMSA, we reveal potential RNP binding sites located in the 5′‐untranslated region of human MOR mRNA. In addition, we also found that morphine‐induced RNPs could regulate MOR expression. Our results establish the role of hnRNP K and PCPB1 in the translational control of morphine‐induced MOR expression in human neuroblastoma (NMB) cells as well as cells stably expressing MOR (NMB1). J. Cell. Physiol. 232: 576–584, 2017. © 2016 Wiley Periodicals, Inc. During stimulation, the vast majority of MOR mRNA partitions to the polysomal fraction for synthesis of MOR proteins. These effects are more evident in NMB1 cells, which stably express MOR.